University students' resilience without family financial support : a case study of Indonesian students at IIUM - Umami, Haritsah (Kulliyyah of Education, International Islamic University Malaysia, 2017)
Pursuing higher studies in a foreign country with self-sponsorship is not without problems. However, students who study without sponsorship still thrive and continue their studies. In this regard, resilience plays an important role in helping them recover and develop their capacity to face the problems. This case study explored the Indonesian students' experiences while studying in Malaysia who are devoid of family financial support and any other forms of sponsorship. This study also uncovered factors that help them to survive despite the hardships that they face. Furthermore, the study sought to understand how the students cope with the different kinds of difficulties which resultantly contribute to their resilience and survival in this country. Within this objective, three research questions were developed, namely 1) What are the life experiences of the Indonesian students during their studies without family financial support? 2) What are the contributing factors that influence the Indonesian students to achieve resilience? and 3) How do the Indonesian students cope with the financial difficulties in their studies?. Richardson's resilience theory and Bronfenbrenner's ecological theory were used in this study to examine how the Indonesian students achieve resilience as well as the internal and external factors that support resilience. The data collection process included a semi-structured interview with selected four Indonesian students. The data were analysed using the Interpretative phenomenological analysis. The major findings from the data analysis found that the Indonesian students faced various difficult experiences, which began with finding a job to support their financial needs, lack of funds, and the difficulties involved in striking a balance between studying and working. A supportive relationship with families, peers, teachers, and environment were among the important factors that helped the students to achieve resilience. The study also determined that the practice of sharing problems with others and taking meditation were among the strategies used to cope with the difficulties during their studies. Studying without sponsorship was found to give a positive impact on the students on a personal level and in relation to others. The experiences of the selected four Indonesian students served as the evidence that studying without sponsorship can transform students' life in a positive way. In response to the phenomenon, universities must develop interventions focusing on bringing protective factors that increase resilience and make students to feel less stressed in their studies.